Calcium Channel Blockers and Esophageal Sclerosis: Should We Expect Exacerbation of Interstitial Lung Disease - Charalampos Seretis; Fotios Seretis; George Gemenetzis; Nikolaos Liakos; Apostolos Pappas; Stavros Gourgiotis; Emmanuel Lagoudianakis; Dimitrios Keramidaris; Nikolaos Salemis (Case Reports in Gastroenterology, 2012)
Esophageal sclerosis is the most common visceral manifestation of systemic sclerosis, resulting in impaired esophageal clearance and retention of ingested food; in addition, co-existence of lung fibrosis with esophageal scleroderma is not uncommon. Both the progression of generalized connective tissue disorders and the damaging effect of chronic aspiration due to esophageal dysmotility appear to be involved in this procedure of interstitial fibrosis. Nifedipine is a widely prescribed calcium antagonist in a significant percentage of rheumatologic patients suffering from Raynaud syndrome, in order to inhibit peripheral vasospasm. Nevertheless, blocking calcium channels has proven to contribute to exacerbation of gastroesophageal reflux, which consequently can lead to chronic aspiration. We describe the case of severe exacerbation of interstitial lung disease in a 76-year-old female with esophageal sclerosis who was treated with oral nifedipine for Raynaud syndrome.